The talking drums of Nigeria - Akpabot, Samuel (International Library of African Music, 1975)
All the drums found in Nigeria can be broadly grouped under five headings: (1) wooden drum (2) pot drum (3) calabash drum (4) hourglass drum (5) tom-tom drum. Between them, these drum categories span all the ethnic groups in the country. The wooden drum is found only in the Eastern States of Nigeria chiefly among the Ibibios and the Ibos where it is known as obodom or ekwe. The pot drum is also special to the Ibibios, Ibos and Kalahari of the Eastern States. The calabash or gourd drum is only used by the Hausas of Northern Nigeria where it has specific functions. The hourglass drum is the chief musical instrument of the Yorubas of Western Nigeria; varieties of it can be found among the Hausas. The tom-tom drum which is either large or small is used by the Benis and Itsekiris of the Mid-Western State of Nigeria and extensively by the Ibibios, Ibos and Kalabaris of the Eastern States. It does not exist at all in the Northern States although one or two varieties of it are used by the Yorubas of the West for ritual worship.
Keywords: Talking drum; African Music; Nigeria; Talking Drum (Instrument)